Harry Potter and the chamber of secrets [videorecording (Blu-Ray)] - Radcliffe, Daniel, 1989-; Watson, Emma, 1990-; Grint, Rupert, 1988-; Branagh, Kenneth; Harris, Richard, 1930-2002; Smith, Maggie, 1934-; Rickman, Alan; Walters, Julie, 1950-; Isaacs, Jason, 1963-; Cleese, John (Distributed by Warner Home Video, 2002)
Harry, Ron, and Hermione are in their second year at Hogwarts School of Witchcraft and Wizardry and they must use all they have learned so far to ward off attacks from a mysterious dark force. Includes theatrical and extended versions.